Nanjing requiem - Jin, Ha, 1956- (Pantheon Books, 2011)
During the 1937 attack on Nanjing, American missionary and women's college dean Minnie Vautrin decides to remain at her school during a violent Japanese attack that renders the school a refugee center for ten thousand women and children.